IDENTIFIKASI JENIS TANAMAN PENGHASIL BUAH-BUAHAN KOMSUMSI DI PERKARANGAN DESA SUNGAI KAPAS KECAMATAN BANGKO KABUPATEN MERANGIN - Indah Putri Zafira; Leni Marlina; Rivo Yulse Viza (BIOCOLONY, 2022)
Communities in Indonesia generally have a yard where many types of plants grow, such as fruit trees. Fruit-producing plants are plants that are deliberately planted to produce fruit to be consumed in a fresh state. Fruit plants also contain a source of vitamins and protein. Sungai Kapas Village has a fairly large yard of land, fruit plants that live in Sungai Kapas Village have never been studied before, so there is no clearer data and information regarding the types of plants that produce fruit for consumption. This study aims to determine the types of fruit-producing plants for consumption in the gardens of the residents of Sungai Kapas Village. This study used the exploratory method, the fruit plant research results obtained can be used for further cultivation of the types of fruit plants in Sungai Kapas Village, Bangko District, Merangin Regency. From the results of the study it was found that there were 13 species from 12 families of consumption fruit plants found in Sungai Kapas Village.